Careful conversations: an educational video to support parents in communicating about weight with their children - Kody A. Klupt; Stephan M. Oreskovich; Julie Bernard-Genest; Barkha P. Patel; Lisa Chu; Elizabeth Dettmer; Catharine M. Walsh; Michele Strom; Amy C. McPherson; Jonah Strub; Alissa Steinberg; Cathleen Steinegger; et al. (BMC, 2020)
Abstract Background Parents may struggle to initiate healthy weight-related conversations with their children. Educational videos may be an effective tool for improving parents' knowledge and self-efficacy on this topic. The aim of this pilot study was to develop an educational video to assist parents in weight-related conversations with their child, and to assess changes in parents' self-efficacy on this topic. Methods Video development was based on a scoping review and semi-structured interviews with parents. Respondent demographics and user satisfaction were assessed at pre- and post- video, and 4-6 months later. Self-efficacy scores were compared between parent groups based on weight concerns over time. Results Fifty-seven parents participated in the video questionnaires, and 40 repeated measures 4-6 months later. Significant improvements in self-efficacy in "raising the issue of weight" and "answering questions or concerns" were found after watching the video (p ≤ 0.002) compared to baseline, and scores 4-6 months post baseline remained slightly elevated, but non-significant. Parents with concerns about their child being overweight had significantly lower perceived self-efficacy scores compared to parents with no concerns about their child's weight (p = 0.031). The video was found to be positively received and of relevance to parents across a number of different domains. Conclusion(s) Preliminary findings suggest an educational video about initiating weight-related conversations may be an effective tool for increasing parents' perceived self-efficacy in the short term. Further work is needed to validate findings in a randomized controlled trial, and with diverse parent populations. Trial registration ClinicalTrials.gov Identifier: NCT03664492 . Registered 10 September 2018 - Retrospectively registered